Comparação da ação predatória de lambari-bocarra (Oligosarcus argentus) (Pisces-Characidae) e traíra (Hopilas malabaricus) Pisces-Erythrinidae) sobre as formas de jovens tilápia-nilótica (Oreochromis niloticus) (Pisces-Cichlidae) - Rodrigues de Souza, José; de Andrade, Dálcio Ricardo (Revista Ceres, 2025)
This experiment was undertaken as a comparative study of the predation of Oligosarcus argenteus and Hoplias malabaricus on the juvenile stages of the Nile tilapia, Oreochromis niloticus.